Salivary Lactoferrin Expression in a Mouse Model of Alzheimer’s Disease - Antequera, Desiree; Moneo, Diego; Carrero, Laura; Bartolome, Fernando; Ferrer, Isidro; Proctor, Gordon; Carro, Eva (Frontiers in Immunology, 2021)
In the last few years, microbial infection and innate immune theories have been proposed as an alternative approach to understanding the etiopathogenesis of Alzheimer's disease (AD). Lactoferrin, one of the major antimicrobial proteins in saliva, is an important modulator of immune response and inflammation, and represents an important defensive element by inducing a broad spectrum of antimicrobial effects against microbial infections. Our previous works demonstrated that lactoferrin levels in saliva from prodromal and dementia stages of AD patients were decreased compared with healthy subjects. In the present study, we analysed salivary lactoferrin levels in a mouse model of AD. We observed robust and early reduction of lactoferrin levels in saliva from 6-, and 12-months-old APP/PS1 mice. Because saliva is secreted by salivary glands, we hypothesised that dysregulation in salivary glands resulting in reduced salivary lactoferrin levels may occur in AD. To test this idea, we collected submandibular glands from APP/PS1 mice, as well as submandibular gland tissue from AD patients and we analysed the expression levels of key players of the salivary protein expression signalling pathway. A significant reduction in M3 receptor levels was found along with decreased acetylcholine (Ach) levels in submandibular glands from APP/PS1 mice. Similarly, a reduction in M3 receptor levels was observed in human submandibular glands from AD patients but in that case, the Ach levels were found to increase. Our data suggest that the ACh-mediated M3 signalling pathway is impaired in salivary glands in AD, resulting in salivary gland dysfunction and reduced salivary lactoferrin secretion